Report of six cases of fungemia related to health care by Saccharomyces cerevisiae (SC) in a hospital in São Paulo-SP - Gonsalez, Claudio Roberto; Silva, Greice Pereira da; Ralio, Renata Braz; Santos, Nataly Tiago dos; Boccardo, Edison José; Medeiros, Lucas Alberto; Mendonça, Marcelo (Seven Editora, 2023)
Objective: To report six cases of fungemia by Saccharomyces cerevisiae, in patients hospitalized in the Intensive Care Unit of General Hospital of São Paulo/SP/Brazil and the relationship with the use of probiotics. Method: a retrospective survey of data from hospital records. Discussion: Analyzing the 6 cases, we found a mean age of 65.8 years, male predominance (4/6), association with heart disease and lung disease (5/6), use of parenteral diet (3/6), use of venous access (6/6), admission to the Intensive Care Unit (6/6) and use of probiotics (5/6). The correlation between the use of probiotics and the occurrence of fungemia by Saccharomyces cerevisiae seems to be related to factors involved in the probiotic preparation process at the time of its administration to patients. Contamination of surfaces in the hospitalization environment and contamination of central venous accesses by the hands of professionals who handle probiotics during their administration may be the main predisposing factor to these infections. DOI:https://doi.org/ 10.56238/devopinterscie-213